Assessing the determinants of safety culture in the maritime industry - Andrei, Daniela; Grech, M.R.; Griffin, Mark; Neal, A. (2019)
The study approach, findings and the way forward on an Australian Linkage Council funded collaborative research project between the University of Queensland, University of Western Australia and the Australian Maritime Safety Authority, focusing on safety culture will be presented. The aim of the study was to identify the factors that have the strongest impact on safety on board international vessels operating in Australian waters, in order to provide recommendations on how to improve safety in the maritime industry. More than 1,000 seafarers from 197 ships comprising 23 flag States were surveyed. The survey assessed safety culture, work demands, fatigue, mental health, and well-being and safety performance. The results are being used to develop a set of recommendations regarding the best ways to improve safety on board ships. The recommendations centre on a) improving the quality of work procedures; b) introduction of effective fatigue management systems; and c) improving the quality of work design and organisational support. The findings of this study have been presented at a range of industry forums, briefings, and at the International Maritime Organization.